THE INFLUENCE OF SEASON AND TOPOGRAPHY ON MANGANESE (Mn) STATUS OF GRAZING JAVA THIN-TAILED SHEEP IN THE AGRICULTURE AREA IN MIJEN OF SEMARANG-CENTRAL JAVA - Widiyanto, W.; Kusumanti, E.; Mulyono, M.; Surahmanto, S. (Journal of the Indonesian Tropical Animal Agriculture, 2013)
The research was aimed to study the manganese (Mn) status of grazing in Java thin-tailed sheep (JTTS),its interrelation with Mn status in the forages and soil, the influence of seasonal factors and landtopography upon the status of respected mineral. Twenty male JTTS of about 6 months old and 2paddocks with field grass vegetation were used in the research. Treatment factor I was topographynamely plain and slope, while treatment factor II was season, namely dry season and rainy season. Thenumber of experimental sheep was divided into 4 groups with 5 heads of sheep for replication in eachgroup and had been grazed for 2 months. The measured variables were soil pH, Mn content in the soil,forage, feces, and blood plasma. The collected data were processed using analysis of variance withfactorial treatment pattern of 2 X 2 in completely randomized design. Mn level in blood plasma of sheepgrazed on plain and slope paddocks were 0.62 and 0.61 mg/l, respectively, in dry season whereas inrainy season were 0.68 and 0.52 mg/l, respectively. Topography did not influence the level of Mn inblood plasma in dry season. Level of Mn in blood plasma of the sheep was lowest in slope area, whereasin plain area was the highest (P<0.05). Manganese level of soil, forage, feces and blood plasma ofexperimental sheep showed the adequate Mn status.